Kompetensi Kerja Pemerintah di Pemerintah Kelurahan Rurukan I Kecamatan Tomohon Timur - Pongoh, Deasy E. N.; Kaunang, Markus; Goni, Sherly Y. V. I (JURNAL ILMIAH SOCIETY, 2015)
Competence is the ability and characteristics possessed by a civil servant so that civil servants are able to perform their duties in a professional, effective and efficient which includes the provision of services at the village level.This study was carried out to reveal and analyze the competence of employees working in the Village Government Rurukan I Sub East Tomohon This study used qualitative methods. From research conducted found that employees in the Government District of Tomohon Village East Rurukan I have not shown good job competence due to the placement of employees who are not in accordance with the rank and class, educational background that does not comply with existing positions, as well as the employee fails to demonstrate analysis and human relations skills in the work.Keywords: Competence, Employees, Government.